AI-assisted Total Body Dermoscopic Evaluation of Changes in Melanocytic Nevi during Pregnancy: A Prospective, Comparative Study of 2,799 Nevi - Jelissa K. Peter; Fabrice Helfenstein; Sara E. Cerminara; Julia-Tatjana Maul; Mara L. Zehnder; Dagmar Jamiolkowski; Elisabeth Roider; Beda Mühleisen; Irene Hösli; Alexander A. Navarini; Lara V. Maul (Acta Dermato-Venereologica)
Pregnancy-associated changes in melanocytic nevi (MN), apart from size increase on the trunk, remain a topic of debate. We conducted the first prospective study to investigate dermoscopic changes in MN comparing pregnant with non-pregnant women on all body parts using a market-approved convolutional neural network (CNN). We included 25 pregnant and 25 non-pregnant women from Basel, Switzerland, who underwent standard skin cancer screenings and whose MN > 2 mm were digitally recorded and analysed by a CNN. Pregnant women were examined three times: in the first and third trimester and 8–12 weeks postpartum; non-pregnant women twice in an interval of 17–21 weeks. We analysed 2,799 MN. In pregnant women, diameter[p < 0.001], area[p < 0.001], number of colours [p = 0.009], shape asymmetry[p = 0.005] and border sharpness[p = 0.006] (inversely proportional value) increased while ellipseness [p < 0.001] decreased from first trimester to postpartum. Changes occurred mainly during the third trimester to postpartum. Compared to non-pregnant women (only first to third trimester) MN on the upper extremities of pregnant women increased in area[p = 0.011] and diameter[p = 0.025] and decreased in ellipseness[p = 0.037]. MN on the lower extremities increased in area[p = 0.044] and MN on the back increased in colour asymmetry[p = 0.022].